Nonbinary | Leah Corbett SMFA Senior Thesis 2017. - Corbett, Leah. (Tufts Archival Research Center, 2017)
Nonbinary is a photographic wall installation that aims to address the relationship between gender expression and gender identity, and create space for gender non-conforming people to live fully and authentically.; Keywords: nonbinary, gender nonconformity, genderqueer, agender, genderless, medium format film photography, photography, portraiture, environmental protrait, queer, queer portrait, gender binary, queer radicalism, film photography, color fim, Mamiya RZ67, narrative photography, conceptual photography.